2016
DOI: 10.2166/hydro.2016.022
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of an adaptive merging scheme for optimal precipitation estimation over ungauged urban catchment

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms ABSTRACTMerging raingauge-radar data improves the accuracy of precipitation estimation for urban areas. Since the rain gauge network around the ungauged urban catchment is fixed, the relevant research question is about the optimal merging area that produces the best rainfall estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Nanding et al [171] compared radar-gauge rainfall merging methods, such as KED and KRE, and found that the KED produced a better effect and was less affected by the density and configuration of rain gauges. McKee et al [172], Rodriguez et al [173], and Fadhel et al [174] all stated that radar-gauge rainfall merging results were simultaneously decided by multiple factors such as the quality of radar rainfall, the distribution of rain gauges, the merging algorithm, and the precipitation type.…”
Section: Evaluation Of the Merging Effectmentioning
confidence: 99%
“…Nanding et al [171] compared radar-gauge rainfall merging methods, such as KED and KRE, and found that the KED produced a better effect and was less affected by the density and configuration of rain gauges. McKee et al [172], Rodriguez et al [173], and Fadhel et al [174] all stated that radar-gauge rainfall merging results were simultaneously decided by multiple factors such as the quality of radar rainfall, the distribution of rain gauges, the merging algorithm, and the precipitation type.…”
Section: Evaluation Of the Merging Effectmentioning
confidence: 99%